simplest way:
#1, if the roots are 5 and -9, then we have
(x-5)(x+9) = 0
expand this and simplify
x^2 + 4x - 45 = 0
do the others the same way
Solve the following quadratic equation whose roots are.
1)5 and - 9
2)-1 and - 1/2
3)4 and - 11
4)1 and 1 whole number 1/2
2 answers
1)5 and - 9
That means
(x-5)(x+9) = 0
x^2 + 4 x - 45 - 0
if roots are a and b
equation was
(x-a)(x-b) = 0
eg for #4 if you mean 1.5
( x-1) (x- 3/2) = 0
multiply both sides by 2
(x-1)(2x-3) = 0
2 x^2 -5 x + 3 = 0
That means
(x-5)(x+9) = 0
x^2 + 4 x - 45 - 0
if roots are a and b
equation was
(x-a)(x-b) = 0
eg for #4 if you mean 1.5
( x-1) (x- 3/2) = 0
multiply both sides by 2
(x-1)(2x-3) = 0
2 x^2 -5 x + 3 = 0